The Effects of Suburethral Tape on the Symptoms of Overactive Bladder - Hensel, G. (Georg Thieme Verlag KG, 2014)
Suburethral tension-free vaginal tape is used for the treatment of stress urinary incontinence with a high success rate. Often patients report having stress incontinence, as well as co-existing micturition problems which are attributable to overactive bladder syndrome (OAB). The present study examines the effect of suburethral tape on the symptoms of OAB. In the study, we used the transobturator vaginal tape inside-out technique (TVT-O). Materials and Methods: 53 patients were included in the study, all had proven urodynamic stress incontinence and symptoms of overactive bladder. The patients were examined preoperatively and 3 months after the TVT-O placement. Results: The individual OAB symptoms improved significantly, with urinary frequency and urge incontinence improving more than nocturia. The frequency of micturition decreased on average from 16.1 to 10.1 episodes/24 hours, while nocturnal frequency of micturition decreased from 2.2 to 1.1. Not a single patient experienced the simultaneous worsening of all three measured variables, however 19 % of patients did report their simultaneous disappearance. Their quality of life that had been affected by OAB was measured on the basis of validated questionnaires, and found to have improved significantly. Only 28 % of patients reported a desire for drug treatment of OAB symptoms following tape placement. Conclusions: TVT-O placement leads to a significant improvement of the symptoms of overactive bladder syndrome. Patient quality of life – which was affected by OAB – was also enhanced by the tape placement. This accounts for a substantial share of the overall success of the suburethral tape.